The Effectiveness of Using BSI QRIS Mobile Payment as a Transaction Medium for MSMEs in Sawoo District - Wulan Puspita Sari; Husna Ni'matul Ulya (Institut Agama Islam Negeri Ponorogo, 2025)
Introduction: This paper examines the effectiveness of using QRIS BSI as a mobile payment medium for Micro, Small, and Medium Enterprises (MSMEs) in Sawoo District. The topic is important because digital transactions are increasingly essential for improving efficiency and competitiveness among small business actors in Indonesia. Research Methods: This study uses a qualitative descriptive approach with field research methods involving interviews, observations, and documentation. The analysis applies the Technology Acceptance Model (TAM) framework developed by Davis (1986), which includes indicators of usefulness, efficiency, adaptation barriers, and ease of use. Results: The findings show that QRIS BSI provides benefits in efficiency, safety, and modern business image, especially for younger users. However, older customers face limitations due to low digital literacy and unstable internet networks. Conclusion: QRIS BSI is generally effective in improving transaction efficiency and supporting Islamic financial practices, although further improvements in infrastructure and digital literacy are still required.